SISTEM TEORI STIMULUS-RESPON DALAM KESESUAIAN INFLUENCER-PRODUK DAN INTERAKSI MEDIA SOSIAL UNTUK MENINGKATKAN NIAT BELI - Samudra, Abu; Kurniawati, Kurniawati; Masnita, Yolanda (Jurnal Riset Entrepreneurship; Vol 7 No 2 (2024): (Edisi Agustus) Volume 7, Nomor 2, Tahun 2024, 2024)
This study examines the application of stimulus-response theory in the context of product suitability promoted by influencers and social media interactions to increase consumer purchase intention. This research was taken with the population being social media users who follow influencer content. Total population in the study was 193 respondents who were taken using the purposive sampling method. Purposive sampling is a sample withdrawal based on consideration of certain criteria and a sample of 117 respondents was obtained. This research uses SPSS software for validity and reliability tests. After that, researchers used the Structural Equation Modeling (SEM) method to determine the relationship between variables. Data analysis will be carried out using analysis of moment structures (AMOS) software. The results obtained are influencer-product congruence has a significant positive effect on content attributes; social media interaction has a significant positive effect on strategic interaction; content attributes and strategic interaction have a significant positive effect on para social relationships; para social relationships have a significant positive effect on purchase intention. The contribution of the Stimulus-Response Theory system in the context of influencer-product congruence and social media interaction is crucial for designing effective marketing strategies. By leveraging this theory, companies can enhance their understanding of the factors influencing consumer purchase intention and implement more integrated and responsive strategies.